STUDENTS’ MATHEMATICS LEARNING OUTCOMES THROUGH ONLINE LEARNING - Fitriani Nur (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The online learning paradigm becomes an alternative at every level of education today. This study aimed to describe students' mathematics learning outcomes through online learning. The study, which involved 47 students of grade 1 Madrasah Ibtidaiyah, used an observation sheet to collect data related to the online learning. Besides, the documentation of students' mathematics learning outcomes scores was collected to be analyzed by using descriptive statistics. The results of this study indicated that the average score of students’ mathematics learning outcomes through online learning was in the Very Good category. Another finding from this study was that there were still 11% of students who needed mathematics tutoring. Thus, further research could explore the factors that hindered students' current understanding of mathematics learning.